Predictors of COVID-19 vaccine hesitancy in the UK household longitudinal study - Robertson, Elaine; Reeve, Kelly S.; Niedzwiedz, Claire L.; Moore, Jamie; Blake, Margaret; Green, Michael; Katikireddi, Srinivasa Vittal; Benzeval, Michaela J. (Brain, behavior, and immunity, 2021)
•Willingness to be vaccinated was generally high across the UK population.•Vaccine hesitancy exists in population subgroups.•Black and Pakistani/Bangladeshi ethnic groups had higher levels of vaccine hesitancy.•Vaccine hesitancy levels are higher in people with lower education levels.•Focus on ethnic minority and socioeconomic groups is needed during vaccine delivery. Vaccine hesitancy could undermine efforts to control COVID-19. We investigated the prevalence of COVID-19 vaccine hesitancy in the UK and identified vaccine hesitant subgroups. The ‘Understanding Society’ COVID-19 survey asked participants (n = 12,035) their likelihood of vaccine uptake and reason for hesitancy. Cross-sectional analysis assessed vaccine hesitancy prevalence and logistic regression calculated odds ratios. Overall vaccine hesitancy was low (18% unlikely/very unlikely). Vaccine hesitancy was higher in women (21.0% vs 14.7%), younger age groups (26.5% in 16–24 year olds vs 4.5% in 75 + ) and those with lower education levels (18.6% no qualifications vs 13.2% degree qualified). Vaccine hesitancy was high in Black (71.8%) and Pakistani/Bangladeshi (42.3%) ethnic groups. Odds ratios for vaccine hesitancy were 13.42 (95% CI:6.86, 26.24) in Black and 2.54 (95% CI:1.19, 5.44) in Pakistani/Bangladeshi groups (compared to White British/Irish) and 3.54 (95% CI:2.06, 6.09) for people with no qualifications versus degree. Urgent action to address hesitancy is needed for some but not all ethnic minority groups.